2015
DOI: 10.1007/s11695-015-1929-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Banded and Nonbanded Roux-En-Y Gastric Bypass with 2-Year Follow-Up: a Preliminary Retrospective Analysis

Abstract: The patients with banded gastric bypass had significantly better results in terms of weight loss, weight stability and Gastrointestinal Quality of Life Index scores at 2 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…. Among the articles in PubMed, CENTRAL and Scopus that were retrieved, eight comparative studies were included in the qualitative and quantitative synthesis. The level of agreement between the two reviewers was “good” (κ = 0.635; 95% CI: 0.413, 0.857).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…. Among the articles in PubMed, CENTRAL and Scopus that were retrieved, eight comparative studies were included in the qualitative and quantitative synthesis. The level of agreement between the two reviewers was “good” (κ = 0.635; 95% CI: 0.413, 0.857).…”
Section: Resultsmentioning
confidence: 99%
“…The level of agreement between the two reviewers was “good” (κ = 0.635; 95% CI: 0.413, 0.857). The study design was retrospective in three , prospective in two studies and randomized controlled in three studies . The studies included were conducted in Chile , United States , India , Belgium , Brazil , Mexico and were published between 2007 and 2017.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many factors are probably responsible for the poor outcome after SG, including initial BMI, changes in dietary habits, and sleeve dilation (28)(29)(30). For these reasons, some authors have described implantation of a band or ring around the proximal sleeve pouch to improve weight loss and maintenance as in the BRYGB procedure (31)(32)(33)(34)(35). In our study, the BSG group showed a significant difference compared with the rest reported %EBWL of 66.74% and %TBWL of 38.2% after BSG, which were significantly greater than those in the SG patients in their study.…”
Section: Discussionmentioning
confidence: 99%